Micro-cracking of brittle polycrystalline materials with initial damage - Gulizzi, V.; Benedetti, I. (European Journal of Computational Mechanics, 2016)
In this paper, the effect of pre-existing damage on brittle micro-cracking of polycrystalline materials is explored. The behaviour of single and multiple cracks randomly distributed within a grain scale polycrystalline aggregate is investigated using a recently developed grain boundary 3D computational framework. Each grain is modelled as a single crystal anisotropic domain. Opening, sliding and/or contact at grain boundaries are modelled using nonlinear cohesive-frictional laws. The polycrystalline micro-morphologies are generated using Voronoi tessellation algorithms in combination with a regularisation scheme to avoid the presence of unnecessary small geometrical entities (edges and faces) usually responsible for excessively refined meshes. Additionally, a semi-discontinuous grain boundary mesh within the Boundary Element framework is employed to reduce the computational time and memory storage, while retaining analysis accuracy. To enhance the analysis convergence, a Newton–Raphson scheme is used. The performed numerical tests produce physically sound micro-cracking evolutions, confirming the potential of the technique for multiscale analysis of polycrystalline material damage and failure.